2006
DOI: 10.1111/j.1600-0897.2006.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells During Normal Pregnancy and Pre‐Eclampsia

Abstract: In PE, some factors including Ang II and TNF-alpha stimulated EPC proliferation; however, the impairment of EPC mobilization into systemic circulation by serum factors may contribute to insufficient regeneration of EC in disturbed utero-placental circulation of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 32 publications
6
40
2
Order By: Relevance
“…Gussin et al 9 and Sugawara et al 10 reported that normal pregnancy is associated with mobilisation of EPCs into the circulation, 9 with an increasing number of colony-forming units as a function of gestational age and serum estradiol levels. 10 A progressive increase with gestational age in the concentration of EPCs during pregnancy in healthy women was also observed by Buemi et al 11 Opposite results were found by Matsubara et al 12 and Savvidou et al, 13 showing that normal singleton and twin pregnancies were associated with a trend of decreasing levels of maternal circulating EPCs with advancing gestation as compared with non-pregnant controls.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Gussin et al 9 and Sugawara et al 10 reported that normal pregnancy is associated with mobilisation of EPCs into the circulation, 9 with an increasing number of colony-forming units as a function of gestational age and serum estradiol levels. 10 A progressive increase with gestational age in the concentration of EPCs during pregnancy in healthy women was also observed by Buemi et al 11 Opposite results were found by Matsubara et al 12 and Savvidou et al, 13 showing that normal singleton and twin pregnancies were associated with a trend of decreasing levels of maternal circulating EPCs with advancing gestation as compared with non-pregnant controls.…”
Section: Introductionsupporting
confidence: 53%
“…Such results may be of some help in more appropriately framing our findings in the context of EPCs heterogeneity and the apparently conflicting results in the literature regarding changes in EPCs in normal pregnancy. [9][10][11][12][13] In conclusion, we have shown that mild alteration in glucose tolerance during pregnancy is associated with a reduction in the number of circulating EPCs. This finding together with the reported alterations in multiple cardiovascular risk factors previously observed in women with gestational diabetes emphasises the need for careful follow-up in all women with even modest alterations in glucose tolerance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies in human pregnancies suggest that a mother's EPCs are involved in the physiologic vascular remodeling of systemic and utero-placental circulation (3,4). Hyperglycemia induces dysfunction and apoptosis of EPCs (5); this may impair the development or maturation of the utero-placental circulation, causing maladaptive responses during diabetic pregnancies.…”
mentioning
confidence: 99%